Human dorsolateral prefrontal cortex is involved in visual search for conjunctions but not features: a theta TMS study. - Kalla, R; Muggleton, N; Cowey, A; Walsh, V (2009)
Functional neuroimaging studies have shown that the detection of a target defined by more than one feature (for example, a conjunction of colour and orientation) amongst distractors is associated with the activation of a network of brain areas. Dorsolateral prefrontal cortex (DLPFC), along with areas such as the frontal eye fields (FEF) and posterior parietal cortex (PPC), is a component of this network. While transcranial magnetic stimulation (TMS) had shown that both FEF and PPC are necessary for, and not just correlated with, successful conjunction search, this is not the case for DLPFC. To test the hypothesis that this area is also necessary for efficient conjunction search, TMS was applied over DLPFC and the effects on conjunction and feature (in this case colour) search performance compared with those when TMS was delivered over area MT/V5 and a vertex control stimulation condition. DLPFC TMS impaired performance on the conjunction search task but was without effect on feature search, similar to findings when TMS is delivered over PPC or FEF. Vertex TMS had no effects whereas MT/V5 TMS significantly improved performance with a time course that may indicate that this was due to modulation of V4 activity. These findings illustrate that, like FEF and PPC, DLPFC is necessary for fully effective conjunction visual search performance.